Resistance to PARP-Inhibitors in Cancer Therapy - Montoni, Alicia; Robu, Mihaela; Pouliot, Emilie; Shah, Girish M. (Frontiers in Pharmacology, 2013)
The pharmacological inhibitors of poly(ADP-ribose) polymerase (PARP) family of proteins have shown promising results in preclinical studies and clinical trials as a monotherapy or in combination therapy for some cancers. Thus, usage of PARP-inhibitors (PARPi) in cancer therapy is bound to increase with time, but resistance of cancer cells to PARPi is also beginning to be observed. Here we review different known and potential mechanisms by which: (i) PARPi kill cancer cells; and (ii) cancer cells develop resistance to PARPi. Understanding the lethality caused by PARPi and the countermeasures deployed by cancers cells to survive PARPi will help us rationalize the use of this new class of drugs in cancer therapy.